1992
DOI: 10.1128/aac.36.7.1447
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chromosomal aac(6')-Ic gene from Serratia marcescens

Abstract: The DNA sequence of the chromosomal aac(6')-Ic gene from Serratia marcescens, which had been previously cloned (H. M. Champion, P. M. Bennett, D. A. Lewis, and D. S. Reeves, J. Antimicrob. Chemother. 22:587-596, 1988) was determined. High-pressure liquid chromatographic analysis of extracts prepared from Escherichia coli carrying the chromosomal aac(6')-Ic gene on a plasmid confirmed the presence of 6'-N-acetyltransferase activity in this strain, which was suggested by the aminoglycoside resistance profile. DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
79
1
3

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 27 publications
2
79
1
3
Order By: Relevance
“…The majority of AAC proteins are plasmid encoded; however, an important exception has been identified in Serratia marcescens, in which the 6'-N-acetyltransferase gene [aac(6')-Ic] is chromosomally encoded (4,19,28). Surprisingly, the aac(6')-Ic gene has been shown by DNA hybridization studies to be universally present in S. marcescens strains, regardless of their aminoglycoside resistance profiles (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of AAC proteins are plasmid encoded; however, an important exception has been identified in Serratia marcescens, in which the 6'-N-acetyltransferase gene [aac(6')-Ic] is chromosomally encoded (4,19,28). Surprisingly, the aac(6')-Ic gene has been shown by DNA hybridization studies to be universally present in S. marcescens strains, regardless of their aminoglycoside resistance profiles (28).…”
mentioning
confidence: 99%
“…The majority of AAC proteins are plasmid encoded; however, an important exception has been identified in Serratia marcescens, in which the 6'-N-acetyltransferase gene [aac(6')-Ic] is chromosomally encoded (4,19,28). Surprisingly, the aac(6')-Ic gene has been shown by DNA hybridization studies to be universally present in S. marcescens strains, regardless of their aminoglycoside resistance profiles (28). Although evidence suggests that some aminoglycoside resistance genes originated from producing organisms, such as the actinomycetes (2), it is evident that other genes are intrinsic to gram-negative bacteria, as is the aac(6')-Ic gene in S. marcescens. A second chromosomally encoded acetyltransferase, the 2'-N-acetyltransferase, has been found in Providencia stuartii (6,21,22,33).…”
mentioning
confidence: 99%
“…In gram-negative bacteria, chromosomal acetyltransferases such as the aac(2Ј)-Ia gene product in Providencia stuartii, the aac(6Ј)-Ig gene product in Acinetobacter haemolyticus, and the aac(6Ј)-Ic gene product in Serratia marcescens appear to be intrinsic to these species and confer aminoglycoside resistance when overexpressed (6,30,31,33,40). In P. stuartii, studies on aac(2Ј)-Ia regulation have shown that wild-type strains express the aac(2Ј)-Ia gene at low levels; however, mutants with increased expression can be selected in the presence of aminoglycosides at frequencies of 10 Ϫ6 to 10 Ϫ7 (31).…”
mentioning
confidence: 99%
“…These two genes are chromosomally located and present in all strains of their respective species. The aminoglycoside 6Ј-N-acetyltransferase genes isolated from different bacteria are also chromosomally located and most of them are species-specific as described in Enterococcus faecium (Costa et al, 1993), Serratia marcescens (Shaw et al, 1992), Acinetobacter haemolyticus (Lambert et al, 1993), Acinetobacter sp.13 and Acinetobacter sp.6 (Rudant et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to aminoglycoside modification, another role in other cellular processes or metabolism has been proposed in actinomycetes (Benveniste and Davies, 1973a;Ló pez-Cabrera et al, 1989) and in Providencia (Shaw et al, 1992;Rather et al, 1993) for the chromosomally encoded AAC enzymes. Recently, it has been demonstrated that the enzyme AAC(2Ј)-Ia from P. stuartii contributes to the O-acetylation of peptidoglycan (Payie et al, 1995).…”
Section: Introductionmentioning
confidence: 99%